Learning Maharah Kalam with A Communicative Approach to Arabic Language Education Students at Raden Intan State Islamic University Lampung - Dwi Setia Kurniawan; Fikriansyah (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
It is not easy to learn a language especially a foreign language. Arabic is one of the foreign languages that many people learn in schools and colleges. In society and especially among Muslims, Arabic is seen as a religious language. As for schools and universities, learning Arabic requires the right goals, strategies, techniques, methods, and approaches. This study looked at communicative strategies that are usually taken when teaching Arabic as a foreign language. Students will be able to communicate using the Arabic they have learned in class if they choose a communicative approach to learning Arabic. This will encourage students to be more active participants in the process of learning Arabic. In this study, the method used was field research using a qualitative descriptive approach. Learning Arabic with a communicative approach also pays attention to the characteristics of students who are in the transition period from high school (SMA / MA) to college.